Cerebrovascular Events After No‐Touch Off‐Pump Coronary Artery Bypass Grafting, Conventional Side‐Clamp Off‐Pump Coronary Artery Bypass, and Proximal Anastomotic Devices: A Meta‐Analysis. Issue 2 (18th February 2016) - Pawliszak, Wojciech; Kowalewski, Mariusz; Raffa, Giuseppe Maria; Malvindi, Pietro Giorgio; Kowalkowska, Magdalena Ewa; Szwed, Krzysztof Aleksander; Borkowska, Alina; Kowalewski, Janusz; Anisimowicz, Lech
Abstract : Background: Off‐pump coronary artery bypass (OPCAB) has been shown to reduce the risk of neurologic complications as compared to coronary artery bypass grafting performed with cardiopulmonary bypass. Side‐clamping of the aorta while constructing proximal anastomoses, however, still carries substantial risk of cerebral embolization. We aimed to perform a comprehensive meta‐analysis of studies assessing 2 clampless techniques: aortic "no‐touch" and proximal anastomosis devices (PAD) for OPCAB. Methods and Results: PubMed, CINAHL, CENTRAL, and Google Scholar databases were screened for randomized controlled trials and observational studies comparing "no‐touch" and/or PAD with side‐clamp OPCAB and reporting short‐term (≤30 days) outcomes: cerebrovascular accident and all‐cause mortality. A total of 18 studies (3 randomized controlled trials) enrolling 25 163 patients were included. Aortic "no‐touch" was associated with statistically lower risk of cerebrovascular accident as compared to side‐clamp OPCAB: risk ratio 95% CI: 0.41 (0.27–0.61); P <0.01; I 2 =0%. Event rates were 0.36% and 1.28% for "no‐touch" and side‐clamp OPCAB, respectively. No difference was seen between PAD and side‐clamp OPCAB: 0.71 (0.33–1.55); P =0.39; I 2 =39%. A trend towards increased 30‐day all‐cause mortality with PAD and no difference with "no‐touch" were observed when compared to side‐clamp OPCAB. In a subset analysis, "no‐touch" consistently reduced the risk of cerebrovascular accident regardless of patients' baseline risk characteristics. A benefit with PAD was observed in low‐risk patients. Conclusions: Aortic "no‐touch" technique was associated with nearly 60% lower risk of postoperative cerebrovascular events as compared to conventional side‐clamp OPCAB with effect consistent across patients at different risk.